Does Whipping Tournament Incentives Spur CSR Performance? An Empirical Evidence From Chinese Sub-national Institutional Contingencies - Khan, Muhammad Kaleem; Ali, Shahid; Zahid, R. M. Ammar; Huo, Chunhui; Nazir, Mian Sajid (Frontiers in Psychology, 2022)
Current study investigates whether tournament incentives motivate chief executive officer(s) (CEOs) to be socially responsible. Further, it explores the role of sub-national institutional contingencies (i.e., state-owned enterprises vs. non-SOEs, foreign-owned entities vs. non-FOEs, cross-listed vs. non-cross-listed, developed region) in CEO tournament incentives and the corporate social responsibility performance (CSRP) relationship. Data were collected from all A-shared companies listed in stock exchanges of China for the period of 2014 to 2019. The study uses the baseline methodology of ordinary least squares (OLS) and cluster OLS regression. Moreover, firm-fixed effects regression, two-stage least squares regression, and propensity score matching to deal with the endogeneity problem and check the robustness of the results. The results provide reliable evidence that tournament incentives motivate CEOs to be more socially responsible; whereas, sub-national institutional contingencies positively affect the association between CEO tournament incentives and CSRP. The findings have important implications for companies and regulators who wish to enhance CSP by providing incentives to top managers.